Parental stress increases body mass index trajectory in pre‐adolescents. Issue 6 (5th December 2013) - Shankardass, K.; McConnell, R.; Jerrett, M.; Lam, C.; Wolch, J.; Milam, J.; Gilliland, F.; Berhane, K.
Summary: What is already known about this subject: Rates of childhood obesity have increased since the mid‐1970s. Research into behavioural determinants has focused on physical inactivity and unhealthy diets. Cross‐sectional studies indicate an association between psychological stress experienced by parents and obesity in pre‐adolescents. What this study adds: We provide evidence of a prospective association between parental psychological stress and increased weight gain in pre‐adolescents. Family‐level support for those experiencing chronic stress might help promote healthy diet and exercise behaviours in children. Objective: We examined the impact of parental psychological stress on body mass index (BMI) in pre‐adolescent children over 4 years of follow‐up. Methods: We included 4078 children aged 5–10 years (90% were between 5.5 and 7.5 years) at study entry (2002–2003) in the Children's Health Study, a prospective cohort study in southern California. A multi‐level linear model simultaneously examined the effect of parental stress at study entry on the attained BMI at age 10 and the slope of change across annual measures of BMI during follow‐up, controlled for the child's age and sex. BMI was calculated based on objective measurements of height and weight by trained technicians following a standardized procedure. Results: A two standard deviation increase in parental stress at study entry was associated with an increase in predicted BMI attained by age 10 of 0.287 kg m −2 (95% confidence interval 0.016–0.558; a 2% increase at this age for a participant of average attained BMI). The same increase in parental stress was also associated with an increased trajectory of weight gain over follow‐up, with the slope of change in BMI increased by 0.054 kg m −2 (95% confidence interval 0.007–0.100; a 7% increase in the slope of change for a participant of average BMI trajectory). Conclusions: We prospectively demonstrated a small effect of parental stress on BMI at age 10 and weight gain earlier in life than reported previously. Interventions to address the burden of childhood obesity should address the role of parental stress in children.